Pengaruh Strategi Pembelajaran PBK (Proyek Belajar Karakter) Terhadap Keterampilan Menulis Teks Drama Siswa Kelas XI SMK Swasta Prama Artha Bandar Huluan - Vira Wahyu Ningsih (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to, (1) To analyze students’ skills in writing drama texts using the Character Learning Project strategy for class XI students at Prama Artha Bandar Huluan Private Vocational School. (2) To analyze students’ skills in writing drama texts without using the Character Learning Project strategy for class XI students at Prama Artha Bandar Huluan Private Vocational School. (3) To analyze the influence of the Character Learning Project strategy on the drama text writing skills of Prama Artha Bandar Huluan Private Vocational School class students. The population in this study were class , and writing linguistic rules for drama texts. The method used in this research is a two group posttest design. Data analysis techniques use analysis prerequisite tests, normality tests, and hypothesis tests. The research results in the control class obtained an average of 71.58 and were included in the sufficient category. Meanwhile, the research results used the Character Learning Project strategy 82.19 and were included in the very good category. Through hypothesis testing, namely 2.02 7.57, it can be concluded that there is a significant influence from the use of the Character Learning Project strategy on the Drama Text Writing Skills of Class XI Students of Prama Artha Bandar Huluan Private Vocational School.